A criterion of weak compactness for operators on subspaces of Orlicz spaces. Issue 3 (2008) - Lefèvre Lefèvre, Pascal Pascal; Li Li, Daniel Daniel; Queffélec Queffélec, Hervé Hervé; Rodríguez-Piazza Rodríguez-Piazza, Luis Luis
Abstract : We give a criterion of weak compactness for the operators on the Morse-Transue space M Ψ, the subspace of the Orlicz space L Ψ generated by L ∞ .